Effect of crushing methods on morphology and magnetic properties of anisotropic NdFeB powders - 王仁全 刘颖 李军 储林华 杨晓娇 邱彧冲 (Journal of rare earths, 2017)
Crushing is a critical factor for the anisotropic Nd Fe B powders with high magnetic properties. However, the traditional crushing methods of disk-milling（DM） or impact crushing（IC）, are difficult to obtain high-performance powders. Herein, a new method of preparing anisotropic powders with high performance was reported, which was through crushing the hot-deformed magnets perpendicular to c-axis direction（shear crushing, SC）. The microstructure and alignment of the magnets were examined by scanning electron microscopy（SEM） and X-ray diffraction（XRD）, respectively. The results indicated that the cracks mainly extended along the Nd-rich grain boundary phase and/or the binding interface of ribbons. It not only could protect the magnetic phase from being damaged, but also could keep the grains integrated. Therefore, shear crushing was an effective method for the preparation of highperformance anisotropic powders and then to fabricate the bonded magnets with Br=9.0 kGs, Hci=10.48 kOe and（BH）max=17.7 MGOe.